APPROACHES TO PREVENTION OF DENTAL CARIES IN CHILDREN WITH FLUOROSIS - Sheshukova, O.; Padalka, A.; Trufanova, V.; Polishchuk, T.; Dobroskok, V. (World of Medicine and Biology, 2017)
Prevention of dental caries in children is one of the priorities of the modern dentistry worldwide. It is important to shift the focus of dental practitioners from the restorative approach to dental caries prevention management. This paper describes the caries prevention complex including tooth cleaning with Splat Green Tea toothpaste, BioGaia Prodentis lozenges and Tooth Mousse dental cream application that has been proved to have high caries prevention effectiveness upon the permanent teeth in children living in areas with high fluoride content in drinking water.